KNOWLEDGE, ATTITUDES AND PRACTICES (KAP) ON GOOD MANUFACTURING PRACTICES (GMP) AMONG FOOD HANDLERS IN TERENGGANU HOSPITALS - R., Norhaslinda; H., Norhayati A.; R., Mohd Adzim Khalili (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: This study was conducted to study the level of knowledge, attitudes and practices (KAP) on good manufacturing practices (GMP) among food handlers in Terengganu hospitals. Methods: A cross-sectional study was done with four hospitals involved. Then, sampling method used was purposive convenience sampling. The data had been collected using a method of a questionnaire and being analyzed by using Statistical Package for Social Science (SPSS) 20.0 version. Results: The findings from this study indicate that food handlers in four Terengganu hospitals have a good level of knowledge (83.0±1.51), attitudes (87.2±3.42) and practices (90.7±1.76) regarding GMP. Results show that the association between socio-demographic data factors and variables of level KAP on GMP had significant value. The socio-demographic data involves were gender, ages, working experiences and attendance of training courses. In the other hand, a positive correlation was pointed out for three levels each, between knowledge and attitudes (r=0.13), knowledge and practices (r=0.24), and between attitudes and practices (r=0.42). However, only level practices and attitudes show significant correlation with p<0.05. Conclusion: As the conclusion, effective and compulsory food safety training on a regular and ongoing basis should be highlighted and conducted for all food service employees in order to minimize the prevalence of foodborne hazards.